The Preservation of The Traditional Performing Arts’ Sacred Place - Wahyuningtyas, Bhernadetta Pravita (Bina Nusantara University, 2014)
This study explains the management of “Bharata” reputation, an Icon of classic, legendary, theatrical; traditional performing arts of Indonesia. Puppet has noble values in terms of moral education and philosophy of life; and “Bharata” becomes the